Metode Direct Intruction dalam Penanganan Pertolongan Pertama pada Cedera Kepala - Laviana Nita Ludyanti; Linda Ishariani (STIKES dan AKZI Karya Husada Kediri, 2023)
Head injury is one of the biggest causes of disability and death in society, one of which is students. Providing proper and correct training to students will be able to reduce the incidence of head injuries. The use of the direct instruction method in handling first aid for minor head injuries is an effective way to teach concepts and skills to students. The purpose of this community service is to improve the community's ability to provide first aid treatment for minor head injuries properly and correctly. The target of this activity is 34 students in SMA Negeri 1 Puncu, Kediri Regency. The training was carried out in 2 stages, namely: Stage 1. Providing education on handling first aid for head injuries, while stage 2. Training on handling first aid for head injuries. Based on the results of the evaluation showed that the value of students' knowledge before being given education was 36.63% in the poor category, 3.33% sufficient, and 59.94% good. Meanwhile, after being given education, it shows that 9.99% is sufficient and 89.91% is good. The final result of this community service shows that students are able to carry out first aid treatment for minor head injuries. This community service activity is expected to be a guide for students in providing first aid for minor head injuries. Keywords: Direct Instruction, Head injury